Topological Analysis of the Carbon-Concentrating CETCH Cycle and a Photorespiratory Bypass Reveals Boosted CO2-Sequestration by Plants - Osmanoglu, Özge; Khaled AlSeiari, Mariam; AlKhoori, Hasa Abduljaleel; Shams, Shabana; Bencurova, Elena; Dandekar, Thomas; Naseem, Muhammad (Frontiers in Bioengineering and Biotechnology, 2021)
Synthetically designed alternative photorespiratory pathways increase biomass of tobacco and rice plants. Likewise, some in planta tested synthetic carbon-concentrating cycles (CCCs) hold promise to increase plant biomass while diminishing atmospheric carbon dioxide burden. Taking these individual contributions into account, we hypothesize that the integration of bypasses and CCCs will further increase plant productivity. To test this in silico, we reconstructed a metabolic model by integrating photorespiration and photosynthesis with the synthetically designed alternative pathway 3 (AP3) enzymes and transporters. We calculated fluxes of the native plant system and that of AP3 combined with inhibition of the glycolate/glycerate transporter by using the YANAsquare-package. The activity values corresponding to each enzyme in photosynthesis, photorespiration, and for synthetically designed alternative pathways were estimated. Next, we modelled the effect of crotonyl-CoA/ethylmalonyl-CoA/hydroxybutyryl-CoA cycle (CETCH), which is a set of natural and synthetically designed enzymes that fixes CO₂ manifold more than the native Calvin-Benson-Bassham (CBB) cycle. We compared estimated fluxes across various pathways in the native model and under an introduced CETCH cycle. Moreover, we combined CETCH and AP3-w/plgg1RNAi and calculated the fluxes. We anticipate higher carbon dioxide harvesting potential in plants with AP3-bypass and CETCH-AP3-combination. We discuss the in vivo implementation of these strategies for the improvement of C3 plants and in natural high carbon harvesters.